Impact of IDO1 and IDO2 on the B Cell Immune Response - Merlo, Lauren M. F.; Peng, Weidan; Mandik-Nayak, Laura (Frontiers in Immunology, 2022)
Indoleamine-2,3-dioxygenase (IDO)1 and IDO2 are closely related tryptophan catabolizing enzymes that have immunomodulatory properties. Although initially studied as modifiers of T cell activity, emerging evidence suggests IDO1 and IDO2 also have important roles as modulators of B cell function. In this context, IDO1 and IDO2 appear to play opposite roles, with IDO1 inhibiting and IDO2 driving inflammatory B cell responses. In this mini review, we discuss the evidence for IDO1 and IDO2 modulation of B cell function, focusing on the effect of these enzymes on autoimmunity, allergic responses, protective immunity, and response to pathogens. We summarize strategies to target IDO1 and/or IDO2 as potential therapeutics for inflammatory autoimmune disease and highlight outstanding questions and areas that require future study.